Benchmarking Public-Private Partnerships Procurement 2017 : Assessing Government Capability to Prepare, Procure, and Manage PPPs - World Bank (World Bank, Washington, DC, 2019)
Public-private partnership (PPP) projects are gaining momentum globally as a means for delivering infrastructure. Government capabilities to prepare, procure, and manage such projects are important to ensure that the expected efficiency gains are achieved. No systematic data currently exist to measure those capabilities in governments. Benchmarking PPP Procurement 2017 is the first attempt to collect and present comparable and actionable data on PPP procurement on a large scale, by providing an assessment of the regulatory frameworks and recognized practices that govern PPP procurement across 82 economies. Benchmarking PPP Procurement 2017 presents an analysis of targeted elements aggregated into four areas that cover the main stages of the PPP project cycle:preparation, procurement, and contract management of PPPs, and management of unsolicited proposals (USPs). Using a highway transport project as a case study to ensure cross-comparability, it analyzes the national regulatory frameworks and presents a picture of the procurement landscape at the end of March 2016. The average performance in each area varies across regions and income levels. Figure ES.1 shows that the higher the income level of the group, the higher the performance in the four areas. The data also show that the Organisation for Economic Cooperation and Development (OECD) high income and Latin American and Caribbean regions perform at or above average. Benchmarking PPP Procurement 2017 shows that across the four areas measured, mosteconomies fall short of good practice. In particular, a significant number of economies have low scores in two areas: project preparation and contract management. Consequently, there is room for improvement specially in regulating the activities to be undertaken before launching the PPP procurement process as well as in preparing for those that will follow after the signature of the PPP contract.